Atlantic Slavery: Lost in Trans-lation - Scott L Stabler; Mary Owusu (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2013)
"Who benefited more from the Transatlantic Slave Trade: Ghanaians or Europeans?" Ghana Ministry of Education and Sports:2008, 17). That's the test question on the official government syllabus/standards for Ghanaian schools. The syllabus also lists the benefits of colonization and that list far outweighs the detriments. The lack of a broader understanding about the devastation brought on by the Transatlantic Slave Trade (TAST) is not exclusive to Ghana, but proves similar in the United States and likely throughout the world. Generally, the TAST appears lost in Trans-lation in secondary schools. The Transatlantic Slave Trade forms the most transnational exchange surrounding Africa and the African Diaspora. The TAST to the Americas relocated millions of people, killed untold more, treated them as property based on their melanin, caused many wars and affects the world today. To broaden our understanding of the pedagogies of the TAST, Ghanaian secondary teachers were interviewed, textbooks and the national standards were reviewed along with Ghana's role at the heart of the TAST with Cape Coast as a central embarking point. We discovered a lack of instruction about the transnational and contemporary impacts of the TAST at the secondary level. Through our study of the TAST's instruction in Ghana's secondary schools a need to expand how teachers inform students about the breadth of the TAST was discovered. This article will focus primarily on Ghana's lack of transnational reach at the secondary school level due to the limits of standardized testing, the Ghana Educational Service's syllabus, the textbooks utilized, assessments, poverty, teacher awareness and neocolonialism. This study also examines why transnational exchange in teaching the TAST proves essential in the secondary school classroom in Ghana and beyond. Ghana Ministry of Education. (2008). Teaching Syllabus for Social Studies Senior High School. Accra: Ghana Ministry of Education and Sports. [i]Teaching Syllabus for Social Studies, Senior High School, Ghana Ministry of Education and Sports, 2008, 17.